Analysis of Within-Test Variability of Non-Destructive Test Methods to Evaluate Compressive Strength of Normal Vibrated and Self-Compacting Concretes - Nepomuceno, Miguel (2018)
Non-destructive tests (NDT) have been used in the last decades for the assessment of in-situ quality and integrity of concrete elements. An important step in the application of NDT methods concerns to the interpretation and validation of the test results. In general, interpretation of NDT results should involve three distinct phases leading to the development of conclusions: processing of collected data, analysis of within-test variability and quantitative evaluation of property under investigation. The analysis of within-test variability can provide valuable information, since this can be compared with that of within-test variability associated with the NDT method in use, either to provide a measure of the quality control or to detect the presence of abnormal circumstances during the in-situ application. This paper reports the analysis of the experimental results of within-test variability of NDT obtained for normal vibrated concrete and self-compacting concrete. The NDT reported includes the surface hardness test, ultrasonic pulse velocity test, penetration resistance test, pull-off test, pull-out test and maturity test. The obtained results are discussed and conclusions are presented.